LEGALITAS USAHA MIKRO KECIL MELALUI NOMOR INDUK BERUSAHA (NIB) - Sarwoko, Endi; Nurfarida, Iva Nurdiana (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
The awareness of Micro, Small Enterprises (MSEs) to have business legality is one of the problems that often occurs in various regions. The Indonesia government is committed to providing convenience in both processes and requirements, one of which is that MSEs only need to have a Nomor Induk Berusaha (NIB). However, the problem that actually occurs is that not all MSEs understand the use of information technology in submitting NIB. The aim of this community service is to to increase understanding of the importance of business legality for MSEs, as well as providing assistance in submitting business legality online. As a result of this service activity, MSEs are aware of the importance of business legality, MSEs will have a Business Identification Number (NIB) as proof of business legality. The long-term benefit expected from legal business ownership is that MSEs gain access to financial institutions to obtain additional capital